2022
DOI: 10.1182/bloodadvances.2021005257
|View full text |Cite
|
Sign up to set email alerts
|

An engineered activated factor V for the prevention and treatment of acute traumatic coagulopathy and bleeding in mice

Abstract: Acute traumatic coagulopathy (ATC) occurs in ≈30% of trauma patients and is associated with increased mortality. Excessive generation of activated protein C (APC) and hyperfibrinolysis are believed to be driving forces for ATC. Two mouse models were used to investigate whether an engineered activated FV variant (superFVa) that is resistant to inactivation by APC and contains a stabilizing A2-A3 domain disulfide bond, is able to reduce traumatic bleeding and normalize hemostasis parameters in ATC. First, ATC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…This finding is perhaps unsurprising given that the PT uses high concentrations of tissue factor that promote clotting within 10-14 s and has little or no capacity to assess clot lysis 35 . Like other investigators using rodent models of ATC/TIC [36][37][38] , we observed a substantial elevation in plasma aPC activity after trauma and haemorrhagic shock. Saline-treated mice exhibited the greatest increase in aPC levels of groups surveyed, an 8.5-fold elevation indicative of an active process, given its magnitude and opposite direction from any dilutional effects.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is perhaps unsurprising given that the PT uses high concentrations of tissue factor that promote clotting within 10-14 s and has little or no capacity to assess clot lysis 35 . Like other investigators using rodent models of ATC/TIC [36][37][38] , we observed a substantial elevation in plasma aPC activity after trauma and haemorrhagic shock. Saline-treated mice exhibited the greatest increase in aPC levels of groups surveyed, an 8.5-fold elevation indicative of an active process, given its magnitude and opposite direction from any dilutional effects.…”
Section: Discussionsupporting
confidence: 87%
“…It is pragmatically focused on our primary research question of which resuscitation fluids restored haemostatic control and ameliorated coagulopathy, and which did not. Others have also modified the original Chesebro et al model to include full anaesthetic coverage in mice and rats 37,38,41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance of SUPER FVa to APC’s anticoagulant effect means that therapeutic strategies based on this recombinant factor are likely to alter the homeostasis process, allowing a longer-term maintenance of FV plasma levels. SUPER FVa’s resistance against inactivation by APC is also an asset in cases of acute traumatic coagulopathy (ATC), characterized by increased levels of APC and hyperfibrinolysis [ 321 ].…”
Section: Homeostasis-modifying Treatments In Coagulationmentioning
confidence: 99%
“…Hemophilia patients with the APC resistant FV Leiden variant were observed to have reduced bleeding (4)(5)(6). Mice with acute traumatic coagulopathy experienced significantly less bleeding when treated with an APCresistant super FVa variant (7). These findings show that APC inhibition promotes a pro-coagulant state.…”
Section: Introductionmentioning
confidence: 91%